A comparison of the CARG tool, the VES-13, and oncologist judgment in predicting grade 3 + toxicities in men undergoing chemotherapy for metastatic prostate cancer. Issue 1 (January 2017) - Alibhai, Shabbir M.H.; Aziz, Salman; Manokumar, Tharsika; Timilshina, Narhari; Breunis, Henriette
Abstract: Objective: Since the benefits of chemotherapy in treating older men with metastatic castration-resistant prostate cancer (mCRPC) are modest, validated tools that predict the risk of treatment toxicity may aid clinical decision-making. Whether these tools are better than oncologist judgment remains unclear. We compared the Cancer and Aging Research Group (CARG) tool, the Vulnerable Elders Survey-13 (VES-13), and oncologist judgment in predicting toxicity in men with mCRPC undergoing chemotherapy. Materials and Methods: Men aged 65 + with mCRPC starting first-line or second-line chemotherapy were enrolled in this prospective observational study. At baseline, VES-13 and CARG risk scores were calculated and treating oncologists were asked to rate toxicity risk on a 10-point scale. Toxicity was captured using the Common Terminology Criteria for Adverse Events version 4. Logistic regression was performed to examine relationships between risk prediction tools and the development of grade 3 + toxicity. Results: 46 patients (mean age 75) were accrued, with most receiving Docetaxel 75 mg/m 2 q3weekly. A total of 9 patients (20%, 95% confidence interval (CI) 9–34%) developed grade 3 + toxicity. Using the CARG tool, 0% (95% CI 0–84%), 17% (95% CI 6–36%), and 27% (95% CI 18–55%) of patients in the low, intermediate, and high risk groups developed grade 3 + toxicity, respectively (p = 0.65). Although the CARG tool, the VES-13, and oncologist judgment appeared to perform similarly, comparisons were limited by the small sample size. Conclusion: Chemotherapy for mCRPC was associated with lower than predicted rates of severe toxicity across all predicted risk groups. Further disease-specific validation studies are warranted.